Evaluation of Sealing Strength in Multilayer LLDPE Packaging for Impact-Resistant Rice Pouches - Henny Irawati; Mas Ayu Elita Hafizah; Azwar Manaf; Bayu Krisnamurti (Jurnal Kimia Sains dan Aplikasi, 2024)
In this study, we evaluate the mechanical integrity, thermal stability, and impact resilience of three different laminated polymer materials—PA/LLDPE, MDO-PE/LLDPE, and BOPE/LLDPE—to assess their suitability for rice packaging applications. Our experiments include tests to determine the temperature at which sealing begins, evaluations of thermal durability, assessments of seal integrity, and impact resistance tests. PA/LLDPE exhibited excellent sealing ability, displaying the highest seal strength of 6,411 gr/15 mm at 150°C, and maintained structural integrity up to 200°C, making it particularly suitable for high-temperature applications. MDO-PE/LLDPE also performed well, especially at lower temperatures, with a seal strength of 5,327 gr/15 mm at 130°C. The addition of a plastomer significantly improved its low-temperature effectiveness. Conversely, BOPE/LLDPE reached its peak seal strength at 3,825 gr/15 mm at 140°C but showed lower stability at higher temperatures. During drop tests, PA/LLDPE and MDO-PE/LLDPE demonstrated good impact resistance, absorbing up to 245.250 Joules, while BOPE/LLDPE absorbed only up to 196.240 Joules, indicating its limited ability to withstand impact. These results suggest that PA/LLDPE and MDO-PE/LLDPE are more effective in preventing environmental ingress, even under stress at temperatures up to 200°C. This research underscores the critical role of polymer composition and structure in enhancing the mechanical performance and durability of packaging materials. The practical applications of these findings are substantial, offering packaging developers insights into selecting appropriate materials that meet industry standards for safety and environmental responsibility, particularly in the food sector. These insights could lead to the development of more sustainable, high-performance packaging solutions, aligning with global trends toward sustainability and safety in food packaging.